PDGF-BB promotes oral submucosal fibrosis by driving phenotypic transformation and autophagy in oral mucosal fibroblasts through downregulation of circHIPK3 - Huamin Zhang; Yutong Zhou; Ni Jian; Canhua Jiang; Qi Wang; Jie Wang (Scientific Reports)
Abstract Circular RNA HIPK3 (circHIPK3), known to regulate cell proliferation, migration, transformation, and autophagy in various fibrotic conditions. However, its role has not been studied in oral submucous fibrosis (OSF). Therefore, we conducted this study to explore whether platelet-derived growth factor-BB (PDGF-BB) induces human oral submucous fibroblasts (hOMF) proliferation, migration, transformation, and autophagy through circHIPK3 regulation. Treatment of hOMFs with PDGF-BB significantly increased circHIPK3 expression, promoting proliferation, migration, and autophagy. While inhibiting circHIPK3 mitigated these effects, confirming its role in PDGF-BB-mediated pathways. These findings reveal that PDGF-BB regulates hOMFs via circHIPK3, contributing to OSF pathogenesis and offering potential therapeutic targets. The molecular characteristics of circHIPK3 in fibroblasts (FBs) were identified by Agarose Gel Electrophoresis, Sanger Sequencing and Actinomycin D assay. Quantitative real-time PCR(RT-qPCR) and Western Blot were used to detect the expression of target molecules. The proliferation and migration capacity of FBs in oral mucosa were detected by the CCK8 and Cell Scratch Assay. Protein molecules interacting with circHIPK3 and downstream signaling pathways were screened by RNA pull down and mass spectrometry. Data are available via ProteomeXchange with identifier PXD062842. Firstly, the ring structure of circHIPK3 is verified. The expression level of circHIPK3 in OSF tissues and hOMFs was significantly decreased, while the expression level of circHIPK3 was significantly increased after inhibition of platelet-derived growth factor receptor beta‌‌ (PDGFR-β) by Imatinib (IMA). Subsequently, it was confirmed that the overexpression of circHIPK3 could effectively inhibit the proliferation, migration, transformation and autophagy of PDGF-BB-induced hOMFs. Finally, the mechanism study showed that circHIPK3 could inhibit the proliferation, migration, transformation and autophagy of hOMFs by regulating Y-box binding protein 1 (YBX1) protein and extracellular regulated protein kinases (ERK), phosphatidylinositol 3-kinase (PI3K) and p38 mitogen-activated protein kinase (p38 MAPK) signaling pathways. PDGF-BB downregulates circHIPK3 expression and induces proliferation, migration, transformation, and autophagy of oral mucosal FBs via the circHIPK3/YBX1 axis and the circHIPK3/ERK, PI3K, p38 MAPK axis.